(untitled) (Teología, 2020)
In his opening address in the present Academic Year of 2009, the Dean of the Faculty, Father Victor Manuel Fernandez, introduced the theme of wisdom and experience in the communication of the Gospel in the horizon of theological vocation. To gain such wisdom one must interweave the contributions of the classical sources and guidance of magisterial teachings, in a simple and profound way, linking theology and communication, wisdom and evangelization, academic education and interior quality, the drama of the world and a reason for hope.